Health financing schemes in Malaysia: the need for the poor and the unemployed / Siti Nur Diyanah Abd. Halim … [et al.] - Abd. Halim, Siti Nur Diyanah; Mohamad Salleh, Nur Nabila; Zakariah, Nurul Jannah; Ishak, Siti Norliyana (Faculty of Law, 2011)
Since independence year in 1957, health sector development programmes have concentrated on improving the health of all Malaysians. The government, which is responsible for providing health care as stipulated in the Federal Constitution, has to ensure a more equitable distribution of services, and improve access to health care. One of the ways to promote good health care is by establishing health financing scheme to every Malaysian. There exist many schemes in Malaysia for workers in public sector and private sector. There is an urgent need to establish similar health financing scheme to the poor and the unemployed. This is to ensure no one will be ostracized in order to enjoy a healthy lifestyle. It is to be noted that the United Kingdom and Singapore have their own health financing schemes that cover all their citizens regardless of their status of life. The main objective of this research is to study the possibility of providing a health financing scheme to the poor and the unemployed in Malaysia by comparing the schemes with the United Kingdom and Singapore. Malaysia should develop its own scheme for the poor and the unemployed and thus uphold its concept of caring society as proposed under the 8 Malaysia Plan.